Pola Tindak Tutur Ekspresif Dalam Komedi Tunggal Di Kompas TV Oleh Marshel Widianto - Hafidz Nur Bhawika; Nanik Setyawati; Icuk Prayogi (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
The research entitled "Expressive Speech Act Patterns in Solo Comedy on Kompas TV by Marshel Widianto" aims to describe the types of expressive speech acts found in Stand Up Comedy YouTube videos by Marshel Widianto on Kompas TV with the data source being Marshel Widianto's YouTube videos on Stand Up Comedy on Kompas TV data is in the form of lingual humor units found in Marshel Widianto's speech when delivering Stand Up Comedy which contains expressive speech acts. In the process of searching and processing data, this research used qualitative descriptive techniques in the form of listening, taking notes and reading and then observing Marshel Widianto's SUC video. This research applies the matching method to determine the meaning of Marshel Widianto's speech which is included in the type of expressive speech act. In this research, 8 types of expressive speech acts were found in the form of congratulating 8 data, saying thank you 3 data, criticizing 13 data, complaining or worrying 8 data, blaming 2 data, praising or flattering 26 data, apologizing 26 data. 1 data, and insinuated 45 data. Based on the data listed, the most dominant type of expressive speech act is sarcasm with 45 data.